Color tunability in green, red and infra-red upconversion emission in Tm3+/Yb3+/Ho3+ co-doped CeO2 with potential application for improvement of efficiency in solar cells - Carvalho, Luiz G. A.; Rocha, Leonardo A.; Buarque, Juliana M. M.; Goncalves, Rogeria Rocha; Nascimento, Clebio S.; Schiavon, Marco A.; Ribeiro, Sidney J. L. [UNESP]; Ferrari, Jefferson L. (Elsevier B.V., 2015)
The preparation of Tm3+/Yb3+/Ho3+ co-doped CeO2 prepared by the precipitation method using ammonium hydroxide as a precursor is presented. By X-ray diffraction the materials show the phase-type of fluorite structure and the crystallite sizes were calculated by the Scherrer's equation. No other phase was observed evincing that the rare earth ions were inserted into the fluorite phase as substitutional or interstitial dopants. The microstrain calculated by the Williamson-Hall method do not show significant changes in their values, indicating that the inclusion of rare earths does not causes structural changes in the CeO2 used as a host matrix. All material showed intense upconversion emission at red and green region under excitation with diode laser at 980 nm. The color of emission changes from green to red with increasing excitation power pump. The materials showed suitable photoluminescent properties for applications as a laser source, solar cells, and great emitter at 800 nm. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: CeO2; Upconversion; Solar cells; Rare earths